Two Models of the Development of Social Withdrawal and Social Anxiety in Childhood and Adolescence: Progress and Blind Spots - Heidi Gazelle (MDPI AG, 2022)
This commentary features a review of two recently reformulated models of the development of child and adolescent: (1) social withdrawal by Rubin and Chronis-Tuscano 2021, and (2) social anxiety by Spence and Rapee 2016. The articles that present these reformulated models now cover advances made during the prior 12 to 18 years of research, including increased knowledge of genetic vulnerability to anxiety and longitudinal patterns of development, and acknowledgement of multiple pathways towards and away from the development of social withdrawal or social anxiety (i.e., equifinality, multifinality). However, these reformulated models also contain several blind spots. The model of social withdrawal development would be improved by explicitly referring to peer treatment (not only attitudinal peer rejection), especially peer exclusion; and incorporating the potential development of clinically significant anxiety in childhood (not only adolescence) and delays in developmental milestones in adulthood. The model of social anxiety development would be improved by featuring social withdrawal as a proximal affective-behavioral profile (rather than a temperament) and drawing upon the literature on social withdrawal and its links to peer relations. Overall, there is a continuing lack of integration between developmental and clinical research and models of the development of social withdrawal and social anxiety.